Pellet preparation method for improving proportion of hematite

By performing surface modification treatment of hematite and developing new composite adhesives, combined with high-voltage electrostatic molding and intelligent temperature-controlled roasting technology, the problem of improving hematite ratio in the existing technology has been solved, and the pellet strength has been improved. The effects of reducing porosity and environmental protection and energy saving.

CN119433191APending Publication Date: 2025-02-14SHANDONG IRON & STEEL GRP YONGFENG LINGANG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411640780.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing pellet preparation technology has many problems in improving the proportion of hematite, resulting in low pellet strength and high porosity, which affects the quality and performance of the pellet.

Method used

By performing surface modification treatment on hematite, a new composite adhesive is developed, and step-by-step addition and gradient addition are used, combining high-voltage electrostatic molding technology and intelligent temperature-controlled roasting technology to improve the quality and performance of the pellets.

Benefits of technology

It has achieved the improvement of hematite ratio, enhanced the strength and reduction of pellets, reduced porosity, energy conservation and environmental protection, and reduced energy consumption and pollutant emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433191A_ABST
    Figure CN119433191A_ABST
Patent Text Reader

Abstract

The invention discloses a pellet preparation method for improving the proportion of hematite, and relates to the technical field of sintering processes, and the method comprises the following specific steps: preparing a hematite raw material, crushing and screening the hematite raw material to obtain hematite particles with the particle size range of 0.1-0.5 mm, the hematite raw material chemical components comprise 60% of Fe, 5% of SiO2 and 3% of Al2O3, the surface activity of hematite particles is enhanced through hematite surface modification treatment, the compatibility of the hematite particles and a novel composite binder is greatly improved, the composite binder is composed of modified starch and a derivative of polyvinyl alcohol, and the hematite raw material has the advantages that the surface activity of the hematite particles is improved; by optimizing the proportion and adopting a step-by-step adding mode and a gradient adding mode, the nano-material additive can be more uniformly distributed among hematite particles, the bonding force among the particles is enhanced, meanwhile, the nano-material additive is filled in tiny gaps of the hematite particles, grains are refined, the grain boundary bonding force is enhanced, and the pellet strength is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sintering technology, in particular to a method for preparing pellets with improved hematite proportion. Background Art

[0002] In the modern steel industry, pellets are an important raw material for ironmaking. Their quality and performance have a vital impact on the efficiency, cost and product quality of the entire ironmaking process. Hematite is one of the main raw materials for pellets, and it is of great significance to increase the proportion of hematite in pellets. On the one hand, hematite resources are relatively abundant, and increasing its proportion can make better use of resources; on the other hand, reasonably increasing the proportion of hematite is helpful to improve the metallurgical properties of pellets, thereby improving the efficiency and quality of ironmaking.

[0003] However, in the existing pellet preparation technology, the traditional hematite processing method is relatively simple, which is simply crushing and screening, without surface modification of the hematite particles, making it difficult for the hematite particles to fully combine with the binder during the pellet preparation process. In addition, in the selection and use of the binder, the existing binders, such as a single organic binder or an inorganic binder, often cannot meet the requirements of pellet strength and reducibility at the same time. During pellet forming and roasting, it is difficult to arrange the particles inside the pellet tightly and regularly, resulting in a higher porosity and lower strength of the pellet, affecting the quality and performance of the pellet.

[0004] In summary, the existing pellet preparation technology has many problems in improving the hematite ratio, which limits the further improvement of the quality and performance of the pellets. Therefore, it is of great practical significance and application value to develop a new pellet preparation method to solve the shortcomings of the existing technology, improve the hematite ratio, and prepare high-quality pellets. Summary of the invention

[0005] The purpose of the present invention is to make up for the shortcomings of the prior art and provide a method for preparing pellets with improved hematite ratio. The method can improve the quality of the pellets, enhance their strength and reducibility, reduce porosity, achieve energy conservation and environmental protection, and reduce energy consumption and pollutant emissions by surface modification of the hematite, developing a new composite binder and adopting step-by-step addition and gradient addition methods, combining high-voltage electrostatic forming technology with intelligent temperature control roasting technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing pellets with improved hematite proportion, the specific steps of the method are: S100, preparing a hematite raw material, crushing and screening the raw material to obtain hematite particles with a particle size range of 0.1-0.5 mm; The chemical composition of the hematite raw material includes 60% iron Fe, 5% silicon dioxide SiO2, and 3% aluminum oxide Al2O3; The hematite particles are placed in a reaction container, and a surface modifier solution having a concentration of 5% is added; The surface modifier solution is a polymer containing hydroxyl and carboxyl functional groups; S200, preparing a composite binder, and weighing the modified starch and the derivative of polyvinyl alcohol according to a proportion; Adding the modified starch into water, stirring and dissolving at a temperature of 80° C. to form a uniform solution; and adding the polyvinyl alcohol derivative into the modified starch solution, and continuing stirring for 60 minutes to obtain a composite adhesive; S300, at the initial stage of raw material mixing, the nanomaterial additive is added to the surface-modified hematite particles, after stirring evenly, the environmentally friendly flux is added and placed in the mixing equipment; The additives are nano material additives and environmentally friendly fluxing agents; S400, feeding the raw material with the binder into a high-voltage electrostatic forming device, where the hematite particles are arranged in order under the action of the electric field force to obtain pellets with a certain shape and size; S500, the formed pellets are placed in a roasting furnace, and multiple high-precision temperature sensors and gas analyzers are installed in the roasting furnace; S600, quality inspection of the pellets after roasting, inspection indicators include pellet strength, porosity, and reducibility; If the pellet quality requirements are met, the pellet preparation is completed; If the pellet quality does not meet the standard, the reasons are analyzed and the preparation process parameters are adjusted, and the pellet preparation is repeated.

[0007] Furthermore, during the reaction process, the S100 is controlled at a temperature of 60° C. and a stirring speed of 300 r / min for 30 minutes, so that a uniform coating layer is formed on the surface of the hematite particles. During the surface modification process, the hydroxyl and carboxyl functional groups chemically react with the metal ions on the surface of the hematite particles to form chemical bonds.

[0008] Furthermore, the S200 modified starch and the derivative of polyvinyl alcohol are weighed in a ratio of 3:1.

[0009] Furthermore, the S300 is stirred at 150 r / min, and 30% of the total amount of the composite binder is added at the same time, and as the stirring proceeds, the stirring speed is increased to 300 r / min, and the remaining binder is gradually added during the molding process.

[0010] Furthermore, the nano material additive in S300 is nano-scale magnesium oxide, and nano-magnesium oxide is prepared by a chemical synthesis method using a sol-gel method, wherein magnesium chloride salt is dissolved in an ethanol solution, a complexing agent is added according to a molar ratio of magnesium salt to citric acid complexing agent of 1:1, and the mixture is stirred to form a uniform sol, and nano-scale magnesium oxide particles are obtained by drying at 100° C. and a nitrogen atmosphere and calcining at 500° C. for 2 hours, and the nano-scale magnesium oxide particles are added to a mixing device at a ratio of 1% to 3% of the total mass of the raw materials.

[0011] Furthermore, the environmentally friendly flux in S300 is a composite salt composed of sodium carbonate, potassium carbonate and calcium chloride compounds, wherein the mass ratio of sodium carbonate, potassium carbonate and calcium chloride is 3:2:1. The compounds are placed in a mixing device and fully mixed at 60°C and a stirring speed of 200r / min to prepare an environmentally friendly flux, and the environmentally friendly flux is added to the mixing device at a ratio of 2%-5% of the total mass of the raw materials.

[0012] Furthermore, the S400 sets the voltage of the high-voltage electrostatic generator to 50 kV, the electric field strength to 100 kV / m, controls the molding pressure to 20 MPa and the molding time to 5 min, and controls the ambient humidity to 40%-60% during the molding process.

[0013] Furthermore, the S500 sets the roasting curve through automatic control. During the heating stage, the temperature is raised to 1200°C at 5°C / min, kept warm for 30 minutes, and then cooled to room temperature at 3°C / min. During the roasting process, the heating power and ventilation volume are dynamically adjusted according to the monitoring data of the temperature sensor and the gas analyzer to make the temperature and atmosphere in the furnace uniform and stable.

[0014] Compared with the prior art, the pellet preparation method with improved hematite ratio has the following beneficial effects: 1. The present invention enhances the surface activity of hematite particles through surface modification of hematite, and greatly improves the compatibility with the new composite binder. The composite binder is composed of modified starch and derivatives of polyvinyl alcohol. By optimizing the proportion and adding in steps and gradients, it can be more evenly distributed between the hematite particles to enhance the bonding force between the particles. At the same time, the nanomaterial additive is filled in the tiny gaps of the hematite particles, refines the grains and enhances the grain boundary bonding force, further improving the pellet strength.

[0015] 2. The environmentally friendly flux of the present invention replaces the traditional fluorine-containing flux, which reduces the pellet roasting temperature, saves energy, and reduces pollution to the environment. The intelligent temperature-controlled roasting process accurately controls the roasting process through real-time monitoring and dynamic adjustment of heating power and ventilation volume, which not only reduces energy consumption but also reduces pollutant emissions. In addition, compared with traditional mechanical molding methods, high-voltage electrostatic molding technology reduces the amount of binder used in the surface modification of hematite and further reduces costs.

[0016] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 The present invention is an operation flow chart of a method for preparing pellets with improved hematite proportion. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Embodiment 1 Raw material preparation: Prepare hematite raw material, whose chemical composition includes 60% iron Fe content, 5% silicon dioxide SiO2 content, and 3% aluminum oxide Al2O3 content. Crush and screen it to obtain hematite particles with a particle size range of 0.1-0.5mm.

[0021] Surface modification: The hematite particles were placed in a stainless steel reaction vessel with a capacity of 50 L, and a 5% concentration of a surface modifier solution (a polymer containing hydroxyl and carboxyl functional groups) was added. The reaction was carried out at a temperature of 60°C and a stirring speed of 300 r / min for 30 minutes to form a uniform coating layer on the surface of the hematite particles. The hydroxyl and carboxyl functional groups reacted chemically with the metal ions on the surface of the hematite particles to form chemical bonds, which reduced the surface energy of the hematite particles by 20% and the surface roughness by 30%.

[0022] Preparation and addition of binder: Modified starch and polyvinyl alcohol derivatives are weighed in a mass ratio of 3:1. In an electric stirring device with a speed range of 0-500r / min, the modified starch is added to water, stirred and dissolved at a temperature of 80°C to form a uniform solution; and the polyvinyl alcohol derivative is added to the modified starch solution, and stirring is continued for 60 minutes to obtain a composite binder. At the initial stage of raw material mixing, stirring is performed at 150r / min, and 30% of the total amount of the composite binder is added at the same time. As stirring proceeds, the stirring speed is increased to 300r / min. During the molding process, the remaining binder is gradually added.

[0023] Additive use: Nano-magnesium oxide is selected as the nano-material additive. Nano-magnesium oxide is prepared by a sol-gel method through a chemical synthesis method. Magnesium chloride salt is dissolved in an ethanol solution, and a complexing agent is added according to a molar ratio of magnesium salt to citric acid complexing agent of 1:1, and stirred to form a uniform sol. Nano-magnesium oxide particles are obtained by drying at 100°C and a nitrogen atmosphere and calcining at 500°C for 2 hours. The nano-magnesium oxide particles are added to a mixing device at a ratio of 2% of the total mass of the raw materials. The environmentally friendly flux is a composite salt composed of compounds such as sodium carbonate, potassium carbonate, and calcium chloride, wherein the mass ratio of sodium carbonate, potassium carbonate, and calcium chloride is 3:2:1. These compounds are placed in a ceramic mixing device with a stirring paddle, and are fully mixed at 60°C and a stirring speed of 200r / min to prepare an environmentally friendly flux, and the environmentally friendly flux is added to the mixing device at a ratio of 3% of the total mass of the raw materials.

[0024] Molding: The raw materials with added binder are fed into high-voltage electrostatic molding equipment. Under the action of the electric field force, the hematite particles are tightly and orderly arranged along the direction of the electric field to obtain spherical pellets with a diameter of 10-20 mm. The voltage of the high-voltage electrostatic generator is set to 50 kV, the electric field strength is set to 100 kV / m, the molding pressure is controlled to 20 MPa and the molding time is controlled to 5 min. During the molding process, the ambient humidity is controlled at 40%-60%.

[0025] Roasting: Put the formed pellets into the roasting furnace, install a K-type thermocouple temperature sensor with an accuracy of ±1°C and a gas analyzer with an accuracy of ±0.1% in the roasting furnace, set the roasting curve through automatic control, heat up to 1200°C at 5°C / min in the heating stage, keep warm for 30 minutes, and then cool to room temperature at 3°C / min. During the roasting process, when the temperature sensor detects that the temperature in the furnace is lower than the set value, the automatic control system increases the heating power according to the PID control algorithm; when the gas analyzer detects that the oxygen content in the furnace atmosphere is lower than 5%, the automatic control system increases the ventilation volume according to the preset formula to ensure that the temperature and atmosphere in the furnace are uniform and stable.

[0026] Quality inspection results: The pellets have high strength, with a compressive strength of 35MPa and good wear resistance; the porosity is low, about 12%; the reducibility is good, and under reducing conditions, the reduction degree reaches 85%.

[0027] Embodiment 2 Raw material preparation: prepare hematite raw material, whose chemical composition includes iron Fe content of 60%, silicon dioxide SiO2 content of 5%, and aluminum oxide Al2O3 content of 3%, crush and screen it to obtain hematite particles with a particle size range of 0.1-0.5mm.

[0028] Surface modification: The hematite particles were placed in a stainless steel reaction vessel with a capacity of 50 L, and a 3% concentration of a surface modifier solution (a polymer containing hydroxyl and carboxyl functional groups) was added. The reaction was carried out at a temperature of 60°C and a stirring speed of 300 r / min for 30 minutes to form a uniform coating layer on the surface of the hematite particles. The hydroxyl and carboxyl functional groups reacted chemically with the metal ions on the surface of the hematite particles to form chemical bonds, which reduced the surface energy of the hematite particles by 20% and the surface roughness by 30%.

[0029] Preparation and addition of binder: Modified starch and polyvinyl alcohol derivatives are weighed in a mass ratio of 3:1. In an electric stirring device with a speed range of 0-500r / min, the modified starch is added to water, stirred and dissolved at a temperature of 80°C to form a uniform solution; and the polyvinyl alcohol derivative is added to the modified starch solution, and stirring is continued for 60 minutes to obtain a composite binder. At the initial stage of raw material mixing, stirring is performed at 150r / min, and 30% of the total amount of the composite binder is added at the same time. As stirring proceeds, the stirring speed is increased to 300r / min. During the molding process, the remaining binder is gradually added.

[0030] Additive use: Nano-magnesium oxide is selected as the nano-material additive. Nano-magnesium oxide is prepared by chemical synthesis method and sol-gel method. Magnesium chloride salt is dissolved in ethanol solution, and the complexing agent is added according to the molar ratio of magnesium salt to citric acid complexing agent of 1:1, and stirred to form a uniform sol. Nano-magnesium oxide particles are obtained by drying at 100°C and nitrogen atmosphere and calcining at 500°C for 2h, and the nano-magnesium oxide particles are added to the mixing equipment at a ratio of 2% of the total mass of the raw materials. The environmentally friendly flux is a composite salt composed of sodium carbonate, potassium carbonate, calcium chloride and other compounds, wherein the mass ratio of sodium carbonate, potassium carbonate and calcium chloride is 3:2:1. These compounds are placed in a ceramic mixing equipment with a stirring paddle, and are fully mixed at 60°C and a stirring speed of 200r / min to prepare an environmentally friendly flux, and the environmentally friendly flux is added to the mixing equipment at a ratio of 3% of the total mass of the raw materials.

[0031] Molding: The raw materials with added binder are fed into high-voltage electrostatic molding equipment. Under the action of the electric field force, the hematite particles are tightly and orderly arranged along the direction of the electric field to obtain spherical pellets with a diameter of 10-20 mm. The voltage of the high-voltage electrostatic generator is set to 50 kV, the electric field strength is set to 100 kV / m, the molding pressure is controlled to 20 MPa and the molding time is controlled to 5 min. During the molding process, the ambient humidity is controlled at 40%-60%.

[0032] Roasting: Put the formed pellets into the roasting furnace, install a K-type thermocouple temperature sensor with an accuracy of ±1°C and a gas analyzer with an accuracy of ±0.1% in the roasting furnace, set the roasting curve through automatic control, heat up to 1200°C at 5°C / min in the heating stage, keep warm for 30 minutes, and then cool to room temperature at 3°C / min. During the roasting process, when the temperature sensor detects that the temperature in the furnace is lower than the set value, the automatic control system increases the heating power according to the PID control algorithm; when the gas analyzer detects that the oxygen content in the furnace atmosphere is lower than 5%, the automatic control system increases the ventilation volume according to the preset formula to ensure that the temperature and atmosphere in the furnace are uniform and stable.

[0033] Quality test results: the pellet strength is slightly lower than that of Example 1, the compressive strength is 32 MPa, and the wear resistance is slightly decreased; the porosity is slightly increased, about 14%; the reducibility is basically unchanged, and the reduction degree reaches about 84%.

[0034] Embodiment 3 Raw material preparation: prepare hematite raw material, whose chemical composition includes iron Fe content of 60%, silicon dioxide SiO2 content of 5%, and aluminum oxide Al2O3 content of 3%, crush and screen it to obtain hematite particles with a particle size range of 0.1-0.5mm.

[0035] Surface modification: The hematite particles were placed in a stainless steel reaction vessel with a capacity of 50 L, and a 5% concentration of a surface modifier solution (a polymer containing hydroxyl and carboxyl functional groups) was added. The reaction was carried out at a temperature of 60°C and a stirring speed of 300 r / min for 30 minutes to form a uniform coating layer on the surface of the hematite particles. The hydroxyl and carboxyl functional groups reacted chemically with the metal ions on the surface of the hematite particles to form chemical bonds, which reduced the surface energy of the hematite particles by 20% and the surface roughness by 30%.

[0036] Preparation and addition of binder: Modified starch and derivative of polyvinyl alcohol are weighed in a mass ratio of 2:1. In an electric stirring device with a speed range of 0-500r / min, the modified starch is added to water, stirred and dissolved at a temperature of 80°C to form a uniform solution; and the derivative of polyvinyl alcohol is added to the modified starch solution, and stirring is continued for 60 minutes to obtain a composite binder. At the initial stage of raw material mixing, stirring is performed at 150r / min, and 30% of the total amount of the composite binder is added at the same time. As stirring proceeds, the stirring speed is increased to 300r / min. During the molding process, the remaining binder is gradually added.

[0037] Additive use: Nano-magnesium oxide is selected as the nano-material additive. Nano-magnesium oxide is prepared by a sol-gel method through a chemical synthesis method. Magnesium chloride salt is dissolved in an ethanol solution, and a complexing agent is added according to a molar ratio of magnesium salt to citric acid complexing agent of 1:1, and stirred to form a uniform sol. Nano-magnesium oxide particles are obtained by drying at 100°C and a nitrogen atmosphere and calcining at 500°C for 2 hours. The nano-magnesium oxide particles are added to a mixing device at a ratio of 2% of the total mass of the raw materials. The environmentally friendly flux is a composite salt composed of compounds such as sodium carbonate, potassium carbonate, and calcium chloride, wherein the mass ratio of sodium carbonate, potassium carbonate, and calcium chloride is 3:2:1. These compounds are placed in a ceramic mixing device with a stirring paddle, and are fully mixed at 60°C and a stirring speed of 200r / min to prepare an environmentally friendly flux, and the environmentally friendly flux is added to the mixing device at a ratio of 3% of the total mass of the raw materials.

[0038] Molding: The raw materials with added binder are fed into high-voltage electrostatic molding equipment. Under the action of the electric field force, the hematite particles are tightly and orderly arranged along the direction of the electric field to obtain spherical pellets with a diameter of 10-20 mm. The voltage of the high-voltage electrostatic generator is set to 50 kV, the electric field strength is set to 100 kV / m, the molding pressure is controlled to 20 MPa and the molding time is controlled to 5 min. During the molding process, the ambient humidity is controlled at 40%-60%.

[0039] Roasting: Put the formed pellets into the roasting furnace, install a K-type thermocouple temperature sensor with an accuracy of ±1°C and a gas analyzer with an accuracy of ±0.1% in the roasting furnace, set the roasting curve through automatic control, heat up to 1200°C at 5°C / min in the heating stage, keep warm for 30 minutes, and then cool to room temperature at 3°C / min. During the roasting process, when the temperature sensor detects that the temperature in the furnace is lower than the set value, the automatic control system increases the heating power according to the PID control algorithm; when the gas analyzer detects that the oxygen content in the furnace atmosphere is lower than 5%, the automatic control system increases the ventilation volume according to the preset formula to ensure that the temperature and atmosphere in the furnace are uniform and stable.

[0040] Quality inspection results: The strength of the pellets has changed, the compressive strength is 33MPa, and the wear resistance has also changed accordingly; the porosity remains basically unchanged, about 12%; the reducibility is slightly reduced, and the reduction degree reaches 83%.

[0041] Embodiment 4 Raw material preparation: prepare hematite raw material, whose chemical composition includes iron Fe content of 60%, silicon dioxide SiO2 content of 5%, and aluminum oxide Al2O3 content of 3%, crush and screen it to obtain hematite particles with a particle size range of 0.1-0.5mm.

[0042] Surface modification: The hematite particles were placed in a stainless steel reaction vessel with a capacity of 50 L, and a 5% concentration of a surface modifier solution (a polymer containing hydroxyl and carboxyl functional groups) was added. The reaction was carried out at a temperature of 60°C and a stirring speed of 300 r / min for 30 minutes to form a uniform coating layer on the surface of the hematite particles. The hydroxyl and carboxyl functional groups reacted chemically with the metal ions on the surface of the hematite particles to form chemical bonds, which reduced the surface energy of the hematite particles by 20% and the surface roughness by 30%.

[0043] Preparation and addition of binder: Modified starch and polyvinyl alcohol derivatives are weighed in a mass ratio of 3:1. In an electric stirring device with a speed range of 0-500r / min, the modified starch is added to water, stirred and dissolved at a temperature of 80°C to form a uniform solution; and the polyvinyl alcohol derivative is added to the modified starch solution, and stirring is continued for 60 minutes to obtain a composite binder. At the initial stage of raw material mixing, stirring is performed at 150r / min, and 30% of the total amount of the composite binder is added at the same time. As stirring proceeds, the stirring speed is increased to 300r / min. During the molding process, the remaining binder is gradually added.

[0044] Additive use: Nano-scale titanium oxide is selected as the nanomaterial additive. Nano-titanium oxide is prepared by chemical synthesis using the sol-gel method. Tetrabutyl titanate is dissolved in an ethanol solution, and an appropriate amount of acetylacetone is added as a chelating agent. The solution is stirred to form a uniform sol, which is then dried at 80°C to obtain a dry gel. The dry gel is then calcined at 550°C for 3 hours to obtain nano-scale titanium oxide particles. The nano-scale titanium oxide particles are added to a mixing device at a ratio of 2% of the total mass of the raw materials.

[0045] Molding: The raw materials with added binder are fed into the high-voltage electrostatic molding equipment. Under the action of the electric field force, the hematite particles are closely and orderly arranged along the direction of the electric field to obtain spherical pellets with a diameter of 10-20mm. The voltage of the high-voltage electrostatic generator is set to 50kV, the electric field strength is set to 100kV / m, the molding pressure is controlled to 20MPa and the molding time is controlled to 5min. The ambient humidity is controlled at 40%-60% during the molding process.

[0046] Roasting: Place the formed pellets into the roasting furnace, and install a K-type thermocouple temperature sensor with an accuracy of ±1°C and a gas analyzer with an accuracy of ±0.1% in the roasting furnace. Set the roasting curve through automatic control. During the heating stage, the temperature is raised to 1200°C at 5°C / min, kept warm for 30 minutes, and then cooled to room temperature at 3°C / min. During the roasting process, when the temperature sensor detects that the temperature in the furnace is lower than the set value, the automatic control system increases the heating power according to the PID control algorithm; when the gas analyzer detects that the oxygen content in the furnace atmosphere is lower than 5%, the automatic control system increases the ventilation according to the preset formula to ensure that the temperature and atmosphere in the furnace are uniform and stable.

[0047] Quality test results: the pellet strength is 34 MPa, slightly different from that in Example 1; the porosity is about 13%, higher than that in Example 1; the reducibility reaches 82%, lower than that in Example 1.

[0048] Embodiment 5 Raw material preparation: Prepare hematite raw material, whose chemical composition includes 60% iron Fe content, 5% silicon dioxide SiO2 content, and 3% aluminum oxide Al2O3 content. Crush and screen it to obtain hematite particles with a particle size range of 0.1-0.5mm.

[0049] Surface modification: Place the hematite particles in a stainless steel reaction vessel with a capacity of 50L, and add a 5% concentration of surface modifier solution (polymer containing hydroxyl and carboxyl functional groups). React for 30 minutes at a temperature of 60°C and a stirring speed of 300r / min to form a uniform coating on the surface of the hematite particles. The hydroxyl and carboxyl functional groups react chemically with the metal ions on the surface of the hematite particles to form chemical bonds, which reduces the surface energy of the hematite particles by 20% and the surface roughness by 30%.

[0050] Preparation and addition of binder: Modified starch and derivatives of polyvinyl alcohol are weighed in a mass ratio of 3:1. In an electric stirring device with a speed range of 0-500r / min, the modified starch is added to water, stirred and dissolved at a temperature of 80°C to form a uniform solution; and the derivative of polyvinyl alcohol is added to the modified starch solution, and stirring is continued for 60 minutes to obtain a composite binder. At the initial stage of raw material mixing, stir at 150r / min, and add 30% of the total amount of composite binder at the same time. As stirring proceeds, the stirring speed is increased to 300r / min. During the molding process, the remaining binder is gradually added.

[0051] Additive use: Nano-magnesium oxide is selected as the nano-material additive, and nano-magnesium oxide is prepared by a sol-gel method through a chemical synthesis method. Magnesium chloride salt is dissolved in an ethanol solution, and a complexing agent is added according to a molar ratio of magnesium salt to citric acid complexing agent of 1:1, and stirred to form a uniform sol. Nano-magnesium oxide particles are obtained by drying at 100°C and nitrogen atmosphere and calcining at 500°C for 2h, and the nano-magnesium oxide particles are added to the mixing equipment at a ratio of 2% of the total mass of the raw materials. The environmentally friendly flux is a composite salt composed of compounds such as sodium carbonate, potassium carbonate, and calcium chloride, wherein the mass ratio of sodium carbonate, potassium carbonate, and calcium chloride is 3:2:1. These compounds are placed in a ceramic mixing equipment with a stirring paddle, and are fully mixed at 60°C and a stirring speed of 200r / min to prepare an environmentally friendly flux, and the environmentally friendly flux is added to the mixing equipment at a ratio of 3% of the total mass of the raw materials.

[0052] Molding: The raw materials with added binder are fed into the high-voltage electrostatic molding equipment. Under the action of the electric field force, the hematite particles are closely and orderly arranged along the direction of the electric field to obtain spherical pellets with a diameter of 10-20mm. The voltage of the high-voltage electrostatic generator is set to 40kV, the electric field strength is set to 100kV / m, the molding pressure is controlled to 20MPa and the molding time is controlled to 5min. The ambient humidity is controlled at 40%-60% during the molding process.

[0053] Roasting: Place the formed pellets into the roasting furnace, and install a K-type thermocouple temperature sensor with an accuracy of ±1°C and a gas analyzer with an accuracy of ±0.1% in the roasting furnace. Set the roasting curve through automatic control. During the heating stage, the temperature is raised to 1200°C at 5°C / min, kept warm for 30 minutes, and then cooled to room temperature at 3°C / min. During the roasting process, when the temperature sensor detects that the temperature in the furnace is lower than the set value, the automatic control system increases the heating power according to the PID control algorithm; when the gas analyzer detects that the oxygen content in the furnace atmosphere is lower than 5%, the automatic control system increases the ventilation according to the preset formula to ensure that the temperature and atmosphere in the furnace are uniform and stable.

[0054] Quality inspection results: the pellet strength decreased, the compressive strength was 30MPa, and the wear resistance decreased; the porosity increased to about 15%; the reducibility decreased slightly, and the reduction degree reached 80%.

[0055] Comparative Example Raw material preparation: Prepare hematite raw material, whose chemical composition includes 60% iron Fe content, 5% silicon dioxide SiO2 content, and 3% aluminum oxide Al2O3 content. Crush and screen it to obtain hematite particles with a particle size range of 0.1-0.5mm.

[0056] Surface modification: No surface modification was performed.

[0057] Preparation and addition of binder: A single organic binder (such as polyvinyl alcohol) is used, and the amount added is the conventional amount required to achieve a certain initial strength of the pellets, that is, 5% of the total mass of the raw materials.

[0058] Additives used: No nano material additives and environmentally friendly flux are added.

[0059] Molding: The traditional mechanical molding method is adopted, the molding pressure is 15MPa, and the molding time is 8min.

[0060] Calcination: conventional calcination process was adopted, the temperature and atmosphere were not precisely controlled, the heating rate was 8°C / min, the temperature was raised to 1100°C, the holding time was 20min, and the cooling rate was 5°C / min.

[0061] Quality inspection results: the pellet strength is significantly lower than that of Example 1, the compressive strength is 25 MPa, and the wear resistance is poor; the porosity is relatively high, about 18% (significantly higher than that of Example 1); the reducibility is poor, and the reduction degree reaches 70% (significantly lower than that of Example 1).

[0062] In summary, it can be seen from the quality test results that Example 1 performs relatively well in various indicators; in Example 2, the concentration of the surface modifier is reduced, the pellet strength and porosity indicators deteriorate, and the reducibility remains basically unchanged; after changing the binder component ratio in Example 3, the pellet strength and reducibility have certain changes, and the porosity remains basically unchanged; after replacing the nanomaterial additive with titanium oxide in Example 4, various indicators have changed to varying degrees; in Example 5, the voltage of the high-voltage electrostatic forming equipment is reduced, the pellet strength decreases, the porosity increases, and the reducibility decreases slightly; the various indicators of the comparative example are significantly worse than those of the example, which fully reflects the advantages of this method in the preparation process of pellets with improved hematite ratio, including improving pellet strength, reducing porosity and improving reducibility. The specific data are shown in the following table:

[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing pellets with improved hematite ratio, characterized in that: The specific steps of this method are: S100, preparing a hematite raw material, crushing and screening the raw material to obtain hematite particles with a particle size range of 0.1-0.5 mm; The chemical composition of the hematite raw material includes 60% iron Fe, 5% silicon dioxide SiO2, and 3% aluminum oxide Al2O3; The hematite particles are placed in a reaction container, and a surface modifier solution having a concentration of 5% is added; The surface modifier solution is a polymer containing hydroxyl and carboxyl functional groups; S200, preparing a composite binder, and weighing the modified starch and the derivative of polyvinyl alcohol according to a proportion; Adding the modified starch into water, stirring and dissolving at a temperature of 80° C. to form a uniform solution; and adding the polyvinyl alcohol derivative into the modified starch solution, and continuing stirring for 60 minutes to obtain a composite adhesive; S300, at the initial stage of raw material mixing, the nanomaterial additive is added to the surface-modified hematite particles, after stirring evenly, the environmentally friendly flux is added and placed in the mixing equipment; The additives are nano material additives and environmentally friendly fluxing agents; S400, feeding the raw material with the binder into a high-voltage electrostatic forming device, where the hematite particles are arranged in order under the action of the electric field force to obtain pellets with a certain shape and size; S500, the formed pellets are placed in a roasting furnace, and multiple high-precision temperature sensors and gas analyzers are installed in the roasting furnace; S600, quality inspection of the pellets after roasting, inspection indicators include pellet strength, porosity, and reducibility; If the pellet quality requirements are met, the pellet preparation is completed; If the pellet quality does not meet the standard, the reasons are analyzed and the preparation process parameters are adjusted, and the pellet preparation is repeated.

2. A method for preparing pellets with improved hematite ratio according to claim 1, characterized in that: During the reaction of S100, the temperature is controlled at 60° C. and the stirring speed is 300 r / min for 30 minutes, so that a uniform coating layer is formed on the surface of the hematite particles. During the surface modification process, the hydroxyl and carboxyl functional groups react chemically with the metal ions on the surface of the hematite particles to form chemical bonds.

3. A method for preparing pellets with improved hematite ratio according to claim 1, characterized in that: The S200 modified starch and the derivative of polyvinyl alcohol are weighed in a ratio of 3:

1.

4. A method for preparing pellets with improved hematite ratio according to claim 1, characterized in that: The S300 is stirred at 150 r / min, and 30% of the total amount of the composite binder is added at the same time. As the stirring proceeds, the stirring speed is increased to 300 r / min. During the molding process, the remaining binder is gradually added.

5. A method for preparing pellets with improved hematite ratio according to claim 1, characterized in that: In the S300, the nano material additive is nano-scale magnesium oxide, and the nano-magnesium oxide is prepared by a chemical synthesis method using a sol-gel method. Magnesium chloride salt is dissolved in an ethanol solution, and a complexing agent is added according to a molar ratio of magnesium salt to citric acid complexing agent of 1:1, and stirred to form a uniform sol. Nano-scale magnesium oxide particles are obtained by drying at 100° C. and nitrogen atmosphere and calcining at 500° C. for 2 hours, and the nano-scale magnesium oxide particles are added to a mixing device at a ratio of 1% to 3% of the total mass of the raw materials.

6. The method for preparing pellets with improved hematite ratio according to claim 1, characterized in that: The environmentally friendly flux in S300 is a composite salt composed of sodium carbonate, potassium carbonate and calcium chloride compounds, wherein the mass ratio of sodium carbonate, potassium carbonate and calcium chloride is 3:2:

1. The compounds are placed in a mixing device and fully mixed at 60° C. and a stirring speed of 200 r / min to prepare an environmentally friendly flux, and the environmentally friendly flux is added to the mixing device at a ratio of 2%-5% of the total mass of the raw materials.

7. A method for preparing pellets with improved hematite ratio according to claim 1, characterized in that: The S400 sets the voltage of the high-voltage electrostatic generator to 50 kV, the electric field strength to 100 kV / m, controls the molding pressure to 20 MPa and the molding time to 5 min, and controls the ambient humidity to 40%-60% during the molding process.

8. The method for preparing pellets with improved hematite ratio according to claim 1, characterized in that: The S500 sets the roasting curve through automatic control. During the heating stage, the temperature is raised to 1200°C at 5°C / min, kept at this temperature for 30 minutes, and then cooled to room temperature at 3°C / min. During the roasting process, the heating power and ventilation volume are dynamically adjusted according to the monitoring data of the temperature sensor and the gas analyzer to make the temperature and atmosphere in the furnace uniform and stable.